2014
DOI: 10.3389/fphar.2014.00167
|View full text |Cite
|
Sign up to set email alerts
|

The types of hepatic myofibroblasts contributing to liver fibrosis of different etiologies

Abstract: Liver fibrosis results from dysregulation of normal wound healing, inflammation, activation of myofibroblasts, and deposition of extracellular matrix (ECM). Chronic liver injury causes death of hepatocytes and formation of apoptotic bodies, which in turn, release factors that recruit inflammatory cells (neutrophils, monocytes, macrophages, and lymphocytes) to the injured liver. Hepatic macrophages (Kupffer cells) produce TGFβ1 and other inflammatory cytokines that activate Collagen Type I producing myofibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 164 publications
2
88
0
3
Order By: Relevance
“…The progression of liver fibrosis is promoted by oxidative stress [12,13], although this is likely to be just one of multiple processes involved. In the present study, oxidative stress in the liver of octn1 -/-was much greater than that in wild-type mice at 1 and 2 weeks after treatment with DMN (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progression of liver fibrosis is promoted by oxidative stress [12,13], although this is likely to be just one of multiple processes involved. In the present study, oxidative stress in the liver of octn1 -/-was much greater than that in wild-type mice at 1 and 2 weeks after treatment with DMN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hepatic stellate cells (HSCs) are activated by oxidative stress to collagen-producing myofibroblasts, which promote liver fibrosis by producing ECM [12,13]. Oxidative stress may also injure parenchymal cells, leading to further 6 progression of liver injury.…”
Section: Ergo Is Minimally Taken Up Into Liver Parenchymal Cells Butmentioning
confidence: 99%
See 1 more Smart Citation
“…MFs are capable of expressing a variety of cytoskeletal proteins which are used as markers of their differentiation. MFs contain microfi lament bundles and/or stress fi bers in the cytoplasm which play an important role in the mechanism of contraction that is similar to the mechanism of contraction of smooth-muscle cells [10][11][12].…”
Section: General Characteristics Of Mfsmentioning
confidence: 99%
“…2 Recent studies have shown that myofibroblasts consist of heterogeneous cells, which are derived from different kinds of cells, such as resident fibroblasts, pericytes, epithelial/ endothelial mesenchymal transition-derived cells, and bone marrow-derived fibroblasts (termed fibrocytes). 3,4 Of these cells, accumulating evidence suggest that bone marrow-derived fibroblasts are significantly involved in the pathogenesis of renal fibrosis through (1) recruitment into kidney and (2) differentiation into myofibroblasts. 3 Bone marrow-derived fibroblasts were first identified in the wound chamber model by Bucala et al 5 Bone marrow-derived fibroblasts comprise a minor fraction of the circulating pool of leukocytes (,1%) and share the markers of hematopoietic cells, such as CD45, CD11b, and CD34, as well as mesenchymal cells, including type I collagen (COLI), fibronectin, and platelet-derived growth factor receptor-b.…”
mentioning
confidence: 99%